Microwave-Assisted Synthesis of Boron-Modified TiO2 Nanocrystals - Claudia Carlucci; Barbara Federica Scremin; Teresa Sibillano; Cinzia Giannini; Emanuela Filippo; Patrizia Perulli; Agostina Lina Capodilupo; Giuseppina Anna Corrente; Giuseppe Ciccarella (Inorganics, 2014)
An efficient microwave-assisted synthesis of TiO2:(B) nanorods, using titanium tetraisopropoxide (TTIP), benzyl alcohol as the solvent, together with boric acid and oleic acid as the additive reagents, has been developed. Chemical modification of TTIP by oleic acid was demonstrated as a rational strategy to tune the shape of TiO2 nanocrystals toward nanorod formation. The differently-shaped TiO2:(B) nanocrystals were characterized in detail by transmission electron microscopy (TEM), inductively coupled plasma-atomic emission spectroscopy (ICP-AES), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy and nitrogen absorption-desorption. Oleic acid coordinated on the nanocrystal surface was removed by the reduction of its carboxyl group, and the photocatalytic activity of bare TiO2 nanocrystals, under visible light irradiation, was also evaluated. The synthesized TiO2 anatase nanorods exhibited a good photoactivity and completely degraded Rhodamine B solution within three hours.